The calligraphy book : pointed pen techniques, inspiration, and projects - Bugbee, Lindsey (DK publishing, 2024)
"This all-in-one guide reveals the secret to creating stunning letter art, with essential tips, expert advice, and inspiring projects from Lindsey Bugbee, the creator of The Postman's Knock, the world's number one calligraphy website. Discover the tools you need to achieve the best results: not only pens, nibs, inks, and paper, but also patience and creativity as you build up your confidence and skills. Follow step-by-step guides to Lindsey's favorite lettering styles, then put your new-found skills to use with 15 inspiring projects, including ideas for unique invitations and cards for loved ones. With a little time, practice, and a little ink, you'll be amazed at what you can create."--